Translation of the Composite Abuse Scale (Revised) Short Form (CASR-SF) into isiXhosa - Mankantshu, Buncwanekazi (Rhodes University, Faculty of Humanities, Department of Psychology)
Intimate partner violence (IPV) is a common occurrence in South Africa, yet appropriately validated tools that screen for IPV are not easily available, particularly in African languages. Establishing isiXhosa language versions of screening tools broadens and improves access to mental healthcare services for isiXhosa-speaking groups. This study aimed to develop an isiXhosa language version of the Composite Abuse Scale Revised Short Form (CASR-SF). The CASR-SF is a self-report measure designed to gauge the presence, intensity, and severity of IPV across three domains: physical, psychological, and sexual abuse. Previous translations of this questionnaire indicated its transportability across different languages and contexts, which in addition to the cost and time effectiveness of adapting instead of developing a new questionnaire, led to the decision to translate and adapt it into isiXhosa. The CASR-SF was translated using a four-staged translation design, which included: 1. Forward translation, 2. Back translation, 3. Committee discussion, and 4. Qualitative pilot in a small sample of first language isiXhosa speakers. Four independent translators worked independently to produce the forward and back translation in stages 1 and 2 and the translations team met in stage 3 to discuss and resolve challenging items with the goal of producing an equivalent final isiXhosa version of the CASR-SF. The resulting preliminary version was piloted on a sample of 7 first-language isiXhosa speakers who partook in cognitive interviews as a confirmatory step. The results indicated that for the most part broad concept equivalence was easier to achieve than linguistic equivalence, and participants generally did not struggle with understanding the items. However, questionnaire items on emotions and relatively new terms such as social media were far more complex to translate. African languages such as isiXhosa use metaphors as more respectful/acceptable expressions for topics such as sexual acts, which complicated the translation process at times. There were also various terms that could be used for different English concepts and the aim of this translation was to find one term that would be appropriate and meaningful across different isiXhosa language dialects, which proved challenging at times.
Keywords: Psychological tests -- Translating; Xhosa language; Intimate partner violence; Self report; Translating and interpreting -- Social aspects